THE PRINCIPLE OF PACTA SUNT SERVANDA IN FINTECH TRANSACTIONS IS REVIEWED THROUGH THE PERSPECTIVE OF USHUL FIQH - NUGROHO, WISNU TRI (Universitas Darusssalam Gontor, 2020)
The principle of Pacta Sunt Servanda as part of the legal principle, which is commonly described as